2022
DOI: 10.21037/atm-21-4809
|View full text |Cite
|
Sign up to set email alerts
|

Yinzhihuang oral liquid protects against non-alcoholic steatohepatitis via modulation of the gut-liver axis in mice

Abstract: Background: Yinzhihuang (YZH) oral liquid is a traditional Chinese medicine compound that has emerged as a promising therapeutic agent for non-alcoholic fatty liver disease (NAFLD). Here, we aimed to investigate the therapeutic effects of YZH on non-alcoholic steatohepatitis (NASH) and elucidate its underlying molecular mechanisms.Methods: Mice fed on a high-fat diet plus fructose/glucose drinking water (HFGD) were treated with YZH (30 mL/kg/d). The effects of YZH on mice with NASH were assessed through serolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
(80 reference statements)
0
4
0
Order By: Relevance
“… Zeng, et al (2020) also confirmed that Yinzhihuang liquid (YZHL) can effectively accelerate lipid β oxidation, relieve liver necrotic inflammation, inhibit lipogenesis and relieve oxidative stress, and finally achieve the effect of treating nonalcoholic steatohepatitis in rats. YZHL is also able to regulate the gut-liver axis to prevent the occurrence of NASH in mice, and play a role in reducing body weight, preventing obesity and alleviating hepatocyte steatosis ( Li, et al, 2022 ). The above proprietary Chinese medicines have different degrees of efficacy in the treatment of NAFLD, and are widely used in clinical practice ( Supplementary Table S1 ).…”
Section: Network Pharmacological Study On Non-alcoholic Fatty Liver D...mentioning
confidence: 99%
“… Zeng, et al (2020) also confirmed that Yinzhihuang liquid (YZHL) can effectively accelerate lipid β oxidation, relieve liver necrotic inflammation, inhibit lipogenesis and relieve oxidative stress, and finally achieve the effect of treating nonalcoholic steatohepatitis in rats. YZHL is also able to regulate the gut-liver axis to prevent the occurrence of NASH in mice, and play a role in reducing body weight, preventing obesity and alleviating hepatocyte steatosis ( Li, et al, 2022 ). The above proprietary Chinese medicines have different degrees of efficacy in the treatment of NAFLD, and are widely used in clinical practice ( Supplementary Table S1 ).…”
Section: Network Pharmacological Study On Non-alcoholic Fatty Liver D...mentioning
confidence: 99%
“…The gut dysbiosis could accelerate the development of MAFLD due to abnormal levels of gut microbial metabolites and/or their effects on gut epithelial permeability [ 109 , 110 ]. Therefore, it has been shown that the gut microbiota might play an imperative role in the progression of MAFLD, and gut microbiota dysbiosis may be a significant factor in MAFLD pathogenesis [ 111 , 112 ].…”
Section: Improved Mitophagy With the Modification Of Gut Microbiota F...mentioning
confidence: 99%
“…Certain traditional Chinese medicines, such as Chinese herbs, Chinese herbal formulations, and Chinese patent medicines, have shown effectiveness in reducing hepatic steatosis and inflammation in MAFLD (shown in Table 1) [73‒100].…”
Section: Therapeutic Strategies For Mafld Targeting Tlr4 Signaling Pa...mentioning
confidence: 99%